Sound insulation coating for building and preparation method thereof
By combining chemically modified four-point ZnO whiskers with polyurethane prepolymers, sound insulation coatings for building with high efficiency sound insulation and excellent mechanical properties are prepared, which solves the problems of poor sound insulation effect and low strength of existing coatings, and is suitable for electrostatic sensitive places.
Patent Information
- Application Number
- CN202510021878.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-07
- Publication Date
- 2025-04-01
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing polyurethane coatings for construction have poor sound insulation effect, low strength, and high cost. The four-point ZnO whiskers are not dispersible in resin materials and are prone to agglomeration.
The surface of dimethoxybenzene silane coupling agent and tetra-acid ZnO whiskers are chemically grafted under a nitrogen atmosphere to form diol silicone modified tetra-acid ZnO, added to the polyurethane prepolymer, and mixed with additives such as expanded perlite and sepiolite fibers to form modified polyurethane prepolymers, and finally react with film-forming additives such as thickeners to prepare sound insulation coatings.
It improves the sound insulation effect and mechanical properties of the coating, reduces production costs, and broadens the scope of application, especially in electrostatic sensitive places.
Smart Images

Figure BDA0005231623120000031
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of building materials, in particular to a sound insulation coating for building and a preparation method thereof. Background Art
[0002] In modern society, with the acceleration of urbanization, noise pollution, especially indoor noise pollution, often tiny sounds or vibrations will become serious noise pollution, which has an increasingly serious impact on people's health and daily life. Therefore, the sound insulation effect inside the building has become an important consideration in the design; sound insulation materials can not only improve the indoor sound quality environment, but also play a key role in noise control. How to provide people with a quiet and comfortable living environment through the sound insulation of building materials has received increasing attention. Therefore, the status of the sound insulation function of the building among many building functions has gradually increased.
[0003] There are many kinds of traditional building sound insulation materials, including rock (mineral) wool decorative sound-absorbing panels, perlite decorative sound-absorbing panels, polystyrene foam decorative sound-absorbing panels, metal decorative sound-absorbing panels and micro-perforated structure sound-absorbing panels, etc. However, these materials have many limitations and shortcomings; for example, rock (mineral) wool materials are harmful to the human body and have the risk of cancer if used improperly; polystyrene foam sound-absorbing panels have poor air permeability and heat resistance and will release gases harmful to the human body when exposed to fire; porous metal plate sound-absorbing materials and micro-perforated structure sound-absorbing panels have not been widely used due to their high costs; with the development of the coating industry, sound insulation coatings have emerged. For example, patent No. CN1425720A discloses sound-absorbing and environmentally friendly coatings, which use fly ash beads as lightweight aggregate to improve the sound insulation effect. However, since the pores of the fly ash beads are closed and not transparent, the sound insulation effect of the coating is not ideal.
[0004] Polyurethane has good wear resistance, high elasticity, etc. Its macromolecular main chain contains rigid segments and flexible segments with glass transition temperatures above and below room temperature, which can obtain a relatively ideal damping temperature range and have certain sound insulation performance; however, the sound insulation effect of pure polyurethane coating is limited. Existing technicians have also added microparticles with heat insulation effect (such as aerogel materials) to reduce the projected sound wave energy, thereby playing a role in sound insulation, but its production cost is high, and large-scale production is not used, and polyurethane has the disadvantages of insufficient strength and unstable damping performance; four-needle ZnO whiskers have a unique radial three-dimensional spatial structure, and its network space contains a large number of gaps, which has good absorption of incident sound waves, but when it is added to a resin material, there are problems of poor dispersibility and easy agglomeration. Therefore, how to make full use of the sound absorption characteristics of four-needle ZnO whiskers to provide a low-cost, good sound insulation effect and high mechanical properties polyurethane sound insulation coating is a technical problem that needs to be solved at present. Summary of the invention
[0005] The purpose of the present invention is to overcome the shortcomings of the prior art, provide a sound insulation coating for construction and a preparation method thereof, and solve the problems of poor sound insulation effect and low strength of the existing polyurethane coating for construction.
[0006] To achieve the above object, the technical solution adopted by the present invention is:
[0007] A method for preparing a sound-insulating coating for construction comprises the following steps:
[0008] Step (1), under nitrogen atmosphere, add 70-90 parts of polytetrahydrofuran diol and 10-30 parts of terminal hydroxyl polybutadiene acrylonitrile by weight into a reaction kettle, distill under reduced pressure at a temperature of 110-125° C. and a pressure of 0.05-0.1 MPa for 2-4 hours, cool to 40-50° C., add 4-8 parts of an organic tin catalyst, 3-5 parts of trimethylolpropane and 25-40 parts of isophorone diisocyanate, heat to 75-90° C. and react for 1-3 hours, then add 2-10 parts of diol organosilicon-modified tetrapod-shaped ZnO, continue to react for 0.5-1 hour, add acetone to reduce viscosity, then cool to 45-55° C., add triethylamine to adjust the pH to 8-9, add deionized water, stir evenly, and obtain a modified polyurethane prepolymer.
[0009] Step (2), adding deionized water to 100 parts by weight of the modified polyurethane prepolymer into a high-speed disperser, after uniform dispersion, adding 10-15 parts of expanded perlite, 5-10 parts of sepiolite fiber, 2-5 parts of a thickener, 0.5-1.2 parts of a defoamer and 1-3 parts of a film-forming aid, reacting at 70-90° C. for 1-2 hours to obtain a sound insulation coating for construction.
[0010] Preferably, the organotin catalyst in step (1) is stannous octoate or dibutyltin dilaurate.
[0011] Preferably, the thickener in step (2) is hydroxymethyl cellulose ether or hydroxyethyl cellulose ether.
[0012] Preferably, the film-forming aid in step (2) is dipropylene glycol monobutyl ether or propylene glycol methyl ether acetate.
[0013] Preferably, the method for preparing diol organosilicon-modified tetrapod-shaped ZnO in step (1) comprises the following steps:
[0014] Step S1: Add bis-(4-methoxybenzyl)-amine and methanol to a reaction flask under a nitrogen atmosphere, stir evenly, add allyltrimethoxysilane, stir to react, and after the reaction is completed, reduce pressure and concentrate, and dry to obtain a dimethoxyphenylsilane coupling agent. The preparation reaction formula is as follows:
[0015]
[0016] Step S2, under a nitrogen atmosphere, add tetrapod-shaped ZnO whiskers and ethanol to a reaction flask, and after uniform dispersion, add dimethoxyphenylsilane coupling agent, react at 65-80° C. for 3-8 hours, adjust the pH of the system to 3-5 with glacial acetic acid, filter, wash with ethanol, and dry to obtain dimethoxyphenylsilicone-modified tetrapod-shaped ZnO.
[0017] Step S3, under nitrogen atmosphere, add dimethoxybenzene organosilicon-modified tetrapod-shaped ZnO and dichloromethane into a reaction flask, mix well, add boron tribromide, react at 0-20° C. for 16-32 h, filter, wash with ethanol, and dry to obtain diol organosilicon-modified tetrapod-shaped ZnO.
[0018] Preferably, in step S1, the ratio of bis-(4-methoxybenzyl)-amine, methanol, and allyltrimethoxysilane is 1 g:(5-10) mL:(0.75-0.9) g.
[0019] Preferably, in step S1, the reaction temperature is 50-65° C. and the reaction time is 5-12 h.
[0020] Preferably, in step S2, the ratio of the tetrapod-shaped ZnO whisker, ethanol, and dimethoxyphenylsilane coupling agent is 1 g: (8-12) mL: (0.2-0.4) g.
[0021] Preferably, in step S3, the ratio of dimethoxybenzene organosilicon-modified tetrapod-shaped ZnO, dichloromethane, and boron tribromide is 1 g: (15-25) mL: (2-3.5) g.
[0022] By adopting the above technical solution, the beneficial effects of the present invention are:
[0023] The invention allows bis-(4-methoxybenzyl)-amine and allyltrimethoxysilane to undergo Michael addition reaction to obtain a dimethoxyphenylsilane coupling agent, which is then chemically linked to hydroxyl groups on the surface of a tetrapod-shaped ZnO whisker. Boron tribromide is then used to remove the methoxy groups, which is then used as a chain extender to participate in the synthesis of polyurethane. A modified polyurethane prepolymer is obtained by adding terminal hydroxyl polybutadiene acrylonitrile, which is then uniformly mixed with expanded perlite, sepiolite fiber and related additives to obtain a sound insulation coating for construction.
[0024] Tetrapod-shaped ZnO is loose and soft, with a unique three-dimensional structure forming a mesh space. When sound waves encounter tetrapod-shaped ZnO whiskers, the whiskers' needles overlap or are close to each other to form a large number of gaps. The sound waves will be absorbed by these gaps during propagation. At the same time, the sound wave energy is converted into heat or other forms of energy inside the whiskers, reducing the transmission and reflection of the sound waves. Adding it to polyurethane coatings in the form of chain extenders can play a significant role in sound insulation and noise reduction. The terminal hydroxyl polybutadiene acrylonitrile molecular chain contains two segments, non-polar butadiene and highly polar acrylonitrile, and has the properties of liquid rubber. When sound waves propagate in the material, it will cause molecular vibration and friction inside the material, thereby producing a damping effect, which can more effectively absorb and consume sound wave energy, thereby reducing the transmission efficiency of sound waves and improving the sound insulation effect. After the tetrapod-shaped ZnO whiskers are modified by chemical grafting, the diol groups on their surface can participate in the polymerization reaction of polyurethane, thereby introducing ZnO with good sound insulation performance into the macromolecular chain, so that the prepared architectural coatings have a lasting sound insulation effect.
[0025] The modified four-needle ZnO can be stably dispersed in the polyurethane matrix as a chain extender. Its three-dimensional foot-like structure can act as a skeleton in the matrix and has strong grip. In addition, its needle tip is nanometer-sized and has a strong interaction with the matrix, which can significantly improve the tensile strength of the material. The coating with high elongation at break can better adapt to the slight deformation of the base layer, thereby reducing the risk of cracking. This is because end-hydroxyl polybutadiene acrylonitrile, as a liquid rubber, has excellent flexibility and ductility. Adding it to the coating can effectively improve the flexibility of the coating, so that the coating can more easily deform and return to its original shape when subjected to external force, thereby improving the elongation at break and expanding the scope of application.
[0026] Tetrapod-shaped ZnO whiskers are semiconductor fillers. The tips of the whiskers are very fine, which can easily cause charge concentration under an external electric field. The four needles extend in three dimensions. When adjacent needles approach each other, a conductive path can be formed through the "tunnel effect", allowing the charge to be conducted, thereby reducing the resistivity of the entire composite system. The higher the content of tetrapod-shaped ZnO and the better the dispersion in the polyurethane matrix, the more conducive it is to building a conductive path, making it easier to release the static charge accumulated on the surface of the polyurethane coating, broadening its application in some places sensitive to static electricity, such as laboratories, warehouses and other fields.
[0027] The present invention adds expanded perlite and sepiolite fibers with a porous structure to the coating, and interweaves and bonds them together through liquid rubber emulsion to form a three-dimensional network structure material with certain strength and toughness. The components in the coating work synergistically to achieve a good sound insulation effect, and have excellent mechanical properties and anti-static properties, which greatly broadens its application range. DETAILED DESCRIPTION
[0028] The technical scheme in the embodiment of the present invention will be clearly and completely described below, and it is obvious that the described embodiment is only a part of the embodiment of the present invention, rather than all embodiments. Based on the embodiment in the present invention, all other embodiments obtained by those of ordinary skill in the art without making creative work premise belong to the scope of protection of the present invention. Unless otherwise stated, the raw materials and reagents used in this application are all commercially available products, or can be prepared by known methods.
[0029] Bis-(4-methoxybenzyl)-amine, CAS number is 17061-62-0.
[0030] Allyltrimethoxysilane, CAS number is 2551-83-9.
[0031] Tetrapod-shaped ZnO whiskers, Chengdu Jiaotong University Jingyu Company.
[0032] Hydroxyl-terminated polybutadiene acrylonitrile, hydroxyl value is 0.6125mmol / g, Zibo Qilong Chemical Co., Ltd.
[0033] Example 1
[0034] (1) Under nitrogen atmosphere, 55 g of bis-(4-methoxybenzyl)-amine and 440 mL of methanol were added to a reaction flask, and after stirring, 45.1 g of allyltrimethoxysilane was added, and the mixture was reacted at 60° C. for 8 h. The mixture was concentrated under reduced pressure and dried to obtain a dimethoxyphenylsilane coupling agent.
[0035] (2) Under a nitrogen atmosphere, 50 g of tetrapod-shaped ZnO whiskers and 500 mL of ethanol were added to a reaction flask. After uniform dispersion, 17.5 g of dimethoxyphenylsilane coupling agent was added and reacted at 75° C. for 5 h. The pH of the system was adjusted to 4 with glacial acetic acid. The mixture was filtered, washed with ethanol, and dried to obtain dimethoxyphenylsilicone-modified tetrapod-shaped ZnO.
[0036] (3) Under a nitrogen atmosphere, 45 g of dimethoxybenzene organosilicon-modified tetrapod-shaped ZnO and 900 mL of dichloromethane were added to a reaction flask. After mixing evenly, 117 g of boron tribromide was added and reacted at 10° C. for 24 h. The mixture was filtered, washed with ethanol, and dried to obtain diol organosilicon-modified tetrapod-shaped ZnO.
[0037] (4) Under nitrogen atmosphere, 90 g of polytetrahydrofuran diol and 10 g of terminal hydroxyl polybutadiene acrylonitrile were added to the reaction kettle, and the mixture was distilled under reduced pressure at a temperature of 115° C. and a pressure of 0.08 MPa for 3 h. The mixture was cooled to 45° C., 6 g of stannous octoate, 4 g of trimethylolpropane and 30 g of isophorone diisocyanate were added, and the mixture was heated to 85° C. and reacted for 2 h. Subsequently, 2 g of diol organosilicon-modified tetrapod-shaped ZnO was added, and the reaction was continued for 0.5 h. During the reaction, acetone was added to reduce the viscosity, and the mixture was cooled to 50° C., triethylamine was added to adjust the pH to 9, and deionized water was added. The mixture was stirred evenly to obtain a modified polyurethane prepolymer.
[0038] (5) Add deionized water to 100 g of the modified polyurethane prepolymer in a high-speed disperser, and after uniform dispersion, add 12 g of expanded perlite, 8 g of sepiolite fiber, 3 g of hydroxymethyl cellulose ether, 0.9 g of defoamer BYK-141 and 2 g of dipropylene glycol monobutyl ether, and react at 80° C. for 2 h to obtain a sound insulation coating for construction.
[0039] Example 2
[0040] (1) Under nitrogen atmosphere, 80 g of bis-(4-methoxybenzyl)-amine and 400 mL of methanol were added to a reaction flask, and after stirring, 60 g of allyltrimethoxysilane was added, and the mixture was reacted at 65° C. for 5 h, concentrated under reduced pressure, and dried to obtain a dimethoxyphenylsilane coupling agent.
[0041] (2) Under a nitrogen atmosphere, 75 g of tetrapod-shaped ZnO whiskers and 600 mL of ethanol were added to a reaction flask. After uniform dispersion, 15 g of dimethoxyphenylsilane coupling agent was added and reacted at 80° C. for 3 h. The pH of the system was adjusted to 5 with glacial acetic acid. The mixture was filtered, washed with ethanol, and dried to obtain dimethoxyphenylsilicone-modified tetrapod-shaped ZnO.
[0042] (3) Under nitrogen atmosphere, 70 g of dimethoxybenzene organosilicon-modified tetrapod-shaped ZnO and 1050 mL of dichloromethane were added to a reaction flask, mixed evenly, and then 140 g of boron tribromide was added. The mixture was reacted at 20° C. for 16 h, filtered, washed with ethanol, and dried to obtain diol organosilicon-modified tetrapod-shaped ZnO.
[0043] (4) Under nitrogen atmosphere, 85 g of polytetrahydrofuran diol and 15 g of terminal hydroxyl polybutadiene acrylonitrile were added to a reaction kettle, and the mixture was distilled under reduced pressure at a temperature of 125° C. and a pressure of 0.1 MPa for 2 h. The temperature was lowered to 50° C., 4 g of dibutyltin dilaurate, 3 g of trimethylolpropane and 25 g of isophorone diisocyanate were added, the temperature was raised to 90° C. and the mixture was reacted for 1 h. Subsequently, 4 g of diol organosilicon-modified tetrapod-shaped ZnO was added, and the reaction was continued for 1 h. During the reaction, acetone was added to reduce the viscosity. The mixture was then cooled to 55° C., triethylamine was added to adjust the pH to 8, deionized water was added, and the mixture was stirred evenly to obtain a modified polyurethane prepolymer.
[0044] (5) Add deionized water to 100 g of the modified polyurethane prepolymer in a high-speed disperser, and after uniform dispersion, add 15 g of expanded perlite, 10 g of sepiolite fiber, 5 g of hydroxyethyl cellulose ether, 0.5 g of defoamer BYK-141 and 1 g of propylene glycol methyl ether acetate, and react at 90° C. for 1 h to obtain a sound insulation coating for construction.
[0045] Example 3
[0046] (1) Under nitrogen atmosphere, 35 g of bis-(4-methoxybenzyl)-amine and 350 mL of methanol were added to a reaction flask, stirred evenly, and then 31.5 g of allyltrimethoxysilane was added. The mixture was reacted at 50° C. for 12 h, concentrated under reduced pressure, and dried to obtain a dimethoxyphenylsilane coupling agent.
[0047] (2) Under a nitrogen atmosphere, 30 g of tetrapod-shaped ZnO whiskers and 360 mL of ethanol were added to a reaction flask. After uniform dispersion, 12 g of dimethoxyphenylsilane coupling agent was added and reacted at 65 °C for 8 h. The pH of the system was adjusted to 3 with glacial acetic acid. The mixture was filtered, washed with ethanol, and dried to obtain dimethoxyphenylsilicone-modified tetrapod-shaped ZnO.
[0048] (3) Under nitrogen atmosphere, 25 g of dimethoxybenzene organosilicon-modified tetrapod-shaped ZnO and 625 mL of dichloromethane were added to a reaction flask. After mixing, 87.5 g of boron tribromide was added and reacted at 0° C. for 32 h. The mixture was filtered, washed with ethanol, and dried to obtain diol organosilicon-modified tetrapod-shaped ZnO.
[0049] (4) Under nitrogen atmosphere, 80 g of polytetrahydrofuran diol and 20 g of terminal hydroxyl polybutadiene acrylonitrile were added to the reactor, and the mixture was distilled under reduced pressure at a temperature of 110° C. and a pressure of 0.05 MPa for 4 h. The mixture was cooled to 40° C., 8 g of stannous octoate, 5 g of trimethylolpropane and 40 g of isophorone diisocyanate were added, and the mixture was heated to 75° C. and reacted for 3 h. Subsequently, 6 g of diol organosilicon-modified tetrapod-shaped ZnO was added, and the reaction was continued for 1 h. During the reaction, acetone was added to reduce the viscosity. The mixture was then cooled to 45° C., triethylamine was added to adjust the pH to 8, and deionized water was added. The mixture was stirred evenly to obtain a modified polyurethane prepolymer.
[0050] (5) Add deionized water to 100 g of the modified polyurethane prepolymer in a high-speed disperser, and after uniform dispersion, add 15 g of expanded perlite, 10 g of sepiolite fiber, 5 g of hydroxymethyl cellulose ether, 1.2 g of defoamer BYK-141 and 3 g of dipropylene glycol monobutyl ether, and react at 70° C. for 2 h to obtain a sound insulation coating for construction.
[0051] Example 4
[0052] (1) Under nitrogen atmosphere, 50 g of bis-(4-methoxybenzyl)-amine and 425 mL of methanol were added to a reaction flask. After stirring, 42 g of allyltrimethoxysilane was added. The mixture was reacted at 55° C. for 9 h. The mixture was concentrated under reduced pressure and dried to obtain a dimethoxyphenylsilane coupling agent.
[0053] (2) Under a nitrogen atmosphere, 45 g of tetrapod-shaped ZnO whiskers and 440 mL of ethanol were added to a reaction flask. After uniform dispersion, 16.2 g of dimethoxyphenylsilane coupling agent was added and reacted at 70° C. for 6 h. The pH of the system was adjusted to 4 with glacial acetic acid. The mixture was filtered, washed with ethanol, and dried to obtain dimethoxyphenylsilicone-modified tetrapod-shaped ZnO.
[0054] (3) Under nitrogen atmosphere, 38 g of dimethoxybenzene organosilicon-modified tetrapod-shaped ZnO and 705 mL of dichloromethane were added to a reaction flask. After mixing evenly, 95 g of boron tribromide was added. The mixture was reacted at 5° C. for 18 h. The mixture was filtered, washed with ethanol, and dried to obtain diol organosilicon-modified tetrapod-shaped ZnO.
[0055] (4) Under nitrogen atmosphere, 75 g of polytetrahydrofuran diol and 35 g of terminal hydroxyl polybutadiene acrylonitrile were added to the reaction kettle, and the mixture was distilled under reduced pressure at a temperature of 115° C. and a pressure of 0.09 MPa for 3 h. The temperature was lowered to 45° C., 7 g of dibutyltin dilaurate, 5 g of trimethylolpropane and 35 g of isophorone diisocyanate were added, the temperature was raised to 85° C. and the mixture was reacted for 2 h. Subsequently, 8 g of diol organosilicon-modified tetrapod-shaped ZnO was added, and the reaction was continued for 1 h. During the reaction, acetone was added to reduce the viscosity. The mixture was then cooled to 50° C., triethylamine was added to adjust the pH to 9, deionized water was added, and the mixture was stirred evenly to obtain a modified polyurethane prepolymer.
[0056] (5) Add deionized water to 100 g of the modified polyurethane prepolymer in a high-speed disperser, and after uniform dispersion, add 12 g of expanded perlite, 8 g of sepiolite fiber, 4 g of hydroxyethyl cellulose ether, 1.1 g of defoamer BYK-141 and 2 g of propylene glycol methyl ether acetate, and react at 85° C. for 2 h to obtain a sound insulation coating for construction.
[0057] Example 5
[0058] (1) Under nitrogen atmosphere, 20 g of bis-(4-methoxybenzyl)-amine and 185 mL of methanol were added to a reaction flask, stirred evenly, and then 16.5 g of allyltrimethoxysilane was added. The mixture was reacted at 60° C. for 9 h, concentrated under reduced pressure, and dried to obtain a dimethoxyphenylsilane coupling agent.
[0059] (2) Under a nitrogen atmosphere, 18 g of tetrapod-shaped ZnO whiskers and 170 mL of ethanol were added to a reaction flask. After uniform dispersion, 6.3 g of dimethoxyphenylsilane coupling agent was added and reacted at 70° C. for 6 h. The pH of the system was adjusted to 5 with glacial acetic acid. The mixture was filtered, washed with ethanol, and dried to obtain dimethoxyphenylsilicone-modified tetrapod-shaped ZnO.
[0060] (3) Under nitrogen atmosphere, 15 g of dimethoxybenzene organosilicon-modified tetrapod-shaped ZnO and 330 mL of dichloromethane were added to a reaction flask. After mixing evenly, 42 g of boron tribromide was added. The mixture was reacted at 15° C. for 28 h. The mixture was filtered, washed with ethanol, and dried to obtain diol organosilicon-modified tetrapod-shaped ZnO.
[0061] (4) Under nitrogen atmosphere, 70 g of polytetrahydrofuran diol and 30 g of terminal hydroxyl polybutadiene acrylonitrile were added to the reactor, and the mixture was distilled under reduced pressure at a temperature of 120° C. and a pressure of 0.06 MPa for 4 h. The temperature was lowered to 50° C., 5 g of dibutyltin dilaurate, 5 g of trimethylolpropane and 30 g of isophorone diisocyanate were added, and the mixture was heated to 85° C. and reacted for 3 h. Subsequently, 10 g of diol organosilicon-modified tetrapod-shaped ZnO was added, and the reaction was continued for 0.5 h. During the reaction, acetone was added to reduce the viscosity. The mixture was then cooled to 50° C., triethylamine was added to adjust the pH to 9, and deionized water was added. The mixture was stirred evenly to obtain a modified polyurethane prepolymer.
[0062] (5) Add deionized water to 100 g of the modified polyurethane prepolymer in a high-speed disperser, and after uniform dispersion, add 13 g of expanded perlite, 9 g of sepiolite fiber, 3 g of hydroxyethyl cellulose ether, 1.2 g of defoamer BYK-141 and 3 g of dipropylene glycol monobutyl ether, and react at 85° C. for 2 h to obtain a sound insulation coating for construction.
[0063] Comparative Example 1
[0064] (1) Under nitrogen atmosphere, 90 g of polytetrahydrofuran diol and 10 g of terminal hydroxyl polybutadiene acrylonitrile were added to a reaction kettle, and the mixture was distilled under reduced pressure at a temperature of 115° C. and a pressure of 0.08 MPa for 3 h. The mixture was cooled to 45° C., 6 g of stannous octoate, 4 g of trimethylolpropane and 30 g of isophorone diisocyanate were added, the mixture was heated to 85° C. and reacted for 2 h. Subsequently, 2 g of tetrapod-shaped ZnO whiskers were added, and the reaction was continued for 0.5 h. During the reaction, acetone was added to reduce the viscosity. The mixture was then cooled to 50° C., triethylamine was added to adjust the pH to 9, deionized water was added, and the mixture was stirred evenly to obtain a modified polyurethane prepolymer.
[0065] (2) Add deionized water to 100 g of modified polyurethane prepolymer in a high-speed disperser, and after uniform dispersion, add 12 g of expanded perlite, 8 g of sepiolite fiber, 3 g of hydroxymethyl cellulose ether, 0.9 g of defoamer BYK-141 and 2 g of dipropylene glycol monobutyl ether, and react at 80° C. for 2 h to obtain a building coating.
[0066] Comparative Example 2
[0067] (1) Under nitrogen atmosphere, 100 g of polytetrahydrofuran diol was added to a reaction kettle, and the mixture was distilled under reduced pressure at a temperature of 115° C. and a pressure of 0.08 MPa for 3 h. The mixture was cooled to 45° C., 6 g of stannous octoate, 4 g of trimethylolpropane and 30 g of isophorone diisocyanate were added, the mixture was heated to 85° C. and reacted for 2 h. The reaction was continued for 0.5 h, during which acetone was added to reduce the viscosity. The mixture was then cooled to 50° C., triethylamine was added to adjust the pH to 9, deionized water was added, and the mixture was stirred evenly to obtain a modified polyurethane prepolymer.
[0068] (2) Add deionized water to 100 g of modified polyurethane prepolymer in a high-speed disperser, and after uniform dispersion, add 12 g of expanded perlite, 8 g of sepiolite fiber, 3 g of hydroxymethyl cellulose ether, 0.9 g of defoamer BYK-141 and 2 g of dipropylene glycol monobutyl ether, and react at 80° C. for 2 h to obtain a building coating.
[0069] Impact sound improvement test: The floor is 100mm thick concrete floor, and the coating prepared in this application is evenly sprayed with a spray thickness of 3mm. The sample is sprayed and cured for 7 days after the surface is dry. The test room is 139m 2 During the test, the surface of the sample is paved with bricks, with the upper and lower layers being the same. Wireless building acoustic measurement equipment is used to conduct the test in accordance with the relevant provisions of Part 8 of GB / T19889.8-2022 "Measurement of Sound Insulation of Acoustic Buildings and Building Components".
[0070] Sound insulation level test: Test according to the relevant provisions of GB / T8485-2008 "Grading and testing methods for airborne sound insulation performance of building doors and windows".
[0071] Table 1 Sound insulation performance test
[0072] Impact sound improvement (dB) Sound insulation level (grade) Example 1 65 4 Example 2 62 5 Example 3 58 5 Example 4 53 5 Example 5 51 5 Comparative Example 1 74 3 Comparative Example 2 85 1
[0073] The higher the sound insulation level, the better the sound insulation effect of the coating, and the better it can reduce the impact of external noise on the room. From the test results in the above table, it can be seen that with the increase of the content of diol silicone modified four-needle ZnO, the 3mm thick coating has a gradually enhanced sound insulation effect on the floor, wherein the sound wave in Example 4 drops to 53dB, and the sound insulation level is level 5. This is because on the one hand, the four-needle ZnO is loose and soft, and has a unique three-dimensional structure to form a mesh space. When the sound wave encounters the four-needle ZnO whisker, the needle-shaped bodies of the whisker overlap or are close to each other to form a large number of gaps, and the sound wave will be in the process of propagation. Absorbed by these gaps, the sound wave energy is converted into heat or other forms of energy inside the whiskers, reducing the transmission and reflection of sound waves. Adding it to polyurethane coatings in the form of chain extenders can play a significant role in sound insulation and noise reduction. On the other hand, the terminal hydroxyl polybutadiene acrylonitrile molecular chain contains two segments, non-polar butadiene and highly polar acrylonitrile, which have the properties of liquid rubber. When sound waves propagate in the material, they will cause molecular vibration and friction inside the material, thereby producing a damping effect, which can more effectively absorb and consume sound wave energy, thereby reducing the transmission efficiency of sound waves and improving the sound insulation effect. After the four-needle ZnO whiskers are modified by chemical grafting, the diol groups on their surface can participate in the polymerization reaction of polyurethane, thereby introducing ZnO with good sound insulation performance into the macromolecular chain, so that the prepared architectural coatings have a lasting sound insulation effect. The tetrapod-shaped ZnO whiskers added in Comparative Example 1 have not been surface modified and cannot participate in the synthesis of polyurethane, are prone to agglomeration, and have limited sound insulation performance; Comparative Example 2 does not add tetrapod-shaped ZnO whiskers and terminal hydroxyl polybutadiene acrylonitrile, and has no sound insulation performance.
[0074] Preparation of adhesive film: Pour the coating prepared in the examples and comparative examples into a polytetrafluoroethylene tank, place it horizontally, and air-dry it at room temperature to form a film. Take out the adhesive film, put it in an oven and dry it at 30°C until constant weight, and cool it naturally to obtain the adhesive film to be tested.
[0075] Mechanical property test of the film: the prepared dry film was cut into 25 mm × 4 mm dumbbell-shaped slices, and the film mechanical property test was carried out at room temperature using an electronic universal testing machine with a tensile speed of 200 mm / min. The test was repeated 5 times and the average value was taken.
[0076] Table 2 Mechanical properties test
[0077] Tensile strength(MPa) Elongation at break (%) Example 1 15.4 210.7 Example 2 17.7 265.4 Example 3 20.5 308.2 Example 4 22.8 349.6 Example 5 23.2 352.5 Comparative Example 1 12.9 202.3 Comparative Example 2 10.6 179.0
[0078] It can be seen from the test results in the above table that with the increase of the content of diol silicone modified tetrapod-shaped ZnO, the mechanical properties of the architectural coating are gradually enhanced, wherein the tensile strength in Example 5 is 23.2 MPa, and the elongation at break is 352.5%. This is because, on the one hand, the modified tetrapod-shaped ZnO can be stably dispersed in the polyurethane matrix as a chain extender, and its three-dimensional foot-like structure can act as a skeleton in the matrix, with strong grip, and its needle tip part is nano-sized, which has a strong interaction with the matrix, and can significantly improve the tensile strength of the material; on the other hand, the coating film with high elongation at break can better adapt to the slight deformation of the base layer, thereby reducing the risk of cracking, because terminal hydroxyl polybutadiene acrylonitrile, as a liquid rubber, has excellent flexibility and ductility. Adding it to the coating can effectively improve the flexibility of the coating, so that the coating can be more easily deformed and restored to its original state when subjected to external force, thereby improving the elongation at break and expanding the scope of application.
[0079] Antistatic performance test: tested by broadband dielectric impedance spectrometer, the sample is square, with a side length of 50mm and a thickness of 2mm.
[0080] Table 3 Antistatic performance test
[0081] <![CDATA[Surface resistivity (10 12 Ω)]]> Example 1 185.3 Example 2 126.4 Example 3 63.7 Example 4 22.5 Example 5 16.4 Comparative Example 1 231.0 Comparative Example 2 875.2
[0082] From the test results in the above table, it can be seen that with the increase of the content of diol silicone modified tetrapod-shaped ZnO, the antistatic performance of architectural coatings is gradually enhanced and the surface resistivity is significantly reduced. This is because the tetrapod-shaped ZnO whiskers are semiconductor fillers. The tips of the whiskers are very thin, which can easily cause charge concentration under an external electric field. The four needles extend three-dimensionally. When the adjacent needles are close, a conductive path can be formed through the "tunnel effect", so that the charge can be conducted and the resistivity of the entire composite system can be reduced. The higher the content of tetrapod-shaped ZnO and the better the dispersion in the polyurethane matrix, the more conducive it is to build a conductive path, thereby making it easier to release the static charge accumulated on the surface of the polyurethane coating, broadening its application in some places sensitive to static electricity, such as laboratories, warehouses and other fields.
[0083] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited to the specific details in the above embodiments. Within the technical concept of the present invention, the technical scheme of the present invention can be subjected to a variety of simple modifications, which all belong to the protection scope of the present invention. In the absence of contradiction, they can be combined in any suitable manner. In order to avoid unnecessary repetition, the present invention will not further explain various possible combinations.
Claims
1. A method for preparing a sound-insulating coating for construction, characterized in that: The preparation method comprises the following steps: Step (1), under a nitrogen atmosphere, add 70-90 parts of polytetrahydrofuran diol and 10-30 parts of terminal hydroxyl polybutadiene acrylonitrile by weight to a reaction kettle, distill under reduced pressure at a temperature of 110-125° C. and a pressure of 0.05-0.1 MPa for 2-4 hours, cool to 40-50° C., add 4-8 parts of an organic tin catalyst, 3-5 parts of trimethylolpropane and 25-40 parts of isophorone diisocyanate, heat to 75-90° C. and react for 1-3 hours, then add 2-10 parts of diol organosilicon-modified tetrapod-shaped ZnO, continue to react for 0.5-1 hour, add acetone to reduce viscosity, then cool to 45-55° C., add triethylamine to adjust the pH to 8-9, add deionized water, stir evenly, and obtain a modified polyurethane prepolymer; Step (2), adding deionized water to 100 parts by weight of the modified polyurethane prepolymer into a high-speed disperser, after uniform dispersion, adding 10-15 parts of expanded perlite, 5-10 parts of sepiolite fiber, 2-5 parts of a thickener, 0.5-1.2 parts of a defoamer and 1-3 parts of a film-forming aid, reacting at 70-90° C. for 1-2 hours to obtain a sound insulation coating for construction.
2. The method for preparing the sound-proof coating for construction according to claim 1, characterized in that: The organic tin catalyst in step (1) is stannous octoate or dibutyltin dilaurate.
3. The method for preparing the sound-proof coating for construction according to claim 1, characterized in that: The thickener in step (2) is hydroxymethyl cellulose ether or hydroxyethyl cellulose ether.
4. The method for preparing the sound-proof coating for construction according to claim 1, characterized in that: The film-forming aid in step (2) is dipropylene glycol monobutyl ether or propylene glycol methyl ether acetate.
5. The method for preparing the sound-proof coating for construction according to claim 1, characterized in that: The method for preparing the diol organosilicon-modified tetrapod-shaped ZnO in step (1) comprises the following steps: Step S1, under a nitrogen atmosphere, add bis-(4-methoxybenzyl)-amine and methanol to a reaction flask, stir evenly, add allyltrimethoxysilane, stir to react, after the reaction is completed, reduce pressure and concentrate, and dry to obtain a dimethoxyphenylsilane coupling agent; Step S2, under a nitrogen atmosphere, add tetrapod-shaped ZnO whiskers and ethanol to a reaction flask, and after uniform dispersion, add dimethoxyphenylsilane coupling agent, react at 65-80° C. for 3-8 hours, adjust the pH of the system to 3-5 with glacial acetic acid, filter, wash with ethanol, and dry to obtain dimethoxyphenylsilicone-modified tetrapod-shaped ZnO; Step S3, under nitrogen atmosphere, add dimethoxybenzene organosilicon-modified tetrapod-shaped ZnO and dichloromethane into a reaction flask, mix well, add boron tribromide, react at 0-20° C. for 16-32 h, filter, wash with ethanol, and dry to obtain diol organosilicon-modified tetrapod-shaped ZnO.
6. The method for preparing the sound-proofing coating for construction according to claim 5, characterized in that: In the step S1, the ratio of bis-(4-methoxybenzyl)-amine, methanol, and allyltrimethoxysilane is 1 g:(5-10) mL:(0.75-0.9) g.
7. The method for preparing the sound-proofing coating for construction according to claim 5, characterized in that: In the step S1, the reaction temperature is 50-65° C. and the reaction time is 5-12 h.
8. The method for preparing the sound-proofing coating for construction according to claim 5, characterized in that: In the step S2, the ratio of the tetrapod-shaped ZnO whisker, ethanol, and dimethoxyphenylsilane coupling agent is 1 g: (8-12) mL: (0.2-0.4) g.
9. The method for preparing the sound-proofing coating for construction according to claim 5, characterized in that: In the step S3, the ratio of dimethoxybenzene organosilicon-modified tetrapod-shaped ZnO, dichloromethane, and boron tribromide is 1 g: (15-25) mL: (2-3.5) g.
10. A sound insulation coating for construction, characterized in that: Obtained by the preparation method according to any one of claims 1 to 9.
Citation Information
Patent Citations
Sound absorptive environment protection paint
CN1425720A
Tetrapod-like zinc oxide whisker modified polyurethane resin coating and preparation method thereof
CN110628316A
High-wear-resistance and hydrophilic nano modified polyisocyanate curing agent and preparation method and application thereof
CN112142949A
Single-component polyurethane waterproof coating and preparation method thereof
CN113637406A
Polyurethane sound insulation coating and production process thereof
CN113913098A
Cited By
Porous ceramic sound insulation board and preparation method thereof
CN121292992A